Can objective information update subjective beliefs on sustainable farming? Evidence from a randomized experiment with Japanese rice farmers - Ryosuke Inoue; Kentaro Kawasaki (Ecological Economics, 2026)

SBDyNetVis: a visualization tool of dynamic network for systems biology model - Kentaro Inoue (BioSystems, 2025)

Identification of three QTLs that additively affect heading time in bread wheat (Triticum aestivum L.) by QTL-seq approach - Shoya Komura; Fuminori Kobayashi; Youko Oono; Hirokazu Handa; Yoshihiro Inoue; Kentaro Yoshida (Euphytica, 2024)
Optimizing the timing of heading is crucial for achieving stable production in bread wheat ( Triticum aestivum L.). We analyzed a breeding line, ‘B1-0393’, that headed 5 days earlier than the Japanese elite cultivar ‘Kitahonami’. To identify quantitative trait loci (QTLs) responsible for this difference, we conducted QTL-seq using F 3 progeny of a cross between ‘Kitahonami’ and ‘B1-0393’. We detected QTLs on chromosomes 2D ( QDth.kupg-2D ), 3D ( QDth.kupg-3D ), and 4A ( QDth.kupg-4A ), explaining 10.25%, 2.00%, and 8.24%, respectively, of phenotypic variance. The QDth.kupg-2D locus corresponded to the major photoperiod-regulating gene Photoperiod-D1 ( Ppd-D1 ). ‘Kitahonami’ had the photoperiod-sensitive Ppd-D1b allele and ‘B1-0393’ had the insensitive Ppd-D1a allele. QDth.kupg-4A overlapped with previously reported QTLs, while QDth.kupg-3D was a novel QTL. Segregation analysis using F 2 and F 3 plants confirmed that alleles from ‘B1-0393’ at all three loci accelerated heading and that the three QTLs had additive effects on days to heading. Our findings could be valuable for regulating the timing of heading to optimize wheat yield.

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Changes in fecal microbiota during estrous cycle in healthy thoroughbred mares - Junjie Li; Haruka Toyama; Touko Matsumoto; Mohammad Ibrahim Qasimi; Ryo Inoue; Harutaka Murase; Yuki Yamamoto; Kentaro Nagaoka (Journal of Equine Veterinary Science, 2024)

Unveiling the role of differential growth in 3D morphogenesis: An inference method to analyze area expansion rate distribution in biological systems - Kentaro Morikawa; Shinichi Morita; Kazuki Sakura; Akiteru Maeno; Hiroki Gotoh; Teruyuki Niimi; Yasuhiro Inoue (Journal of Theoretical Biology, 2023)

Condensation flow visualization, heat transfer, and pressure drop in printed circuit heat exchangers with straight and wavy microchannels - Tatsuki Goto; Daisuke Jige; Norihiro Inoue; Kentaro Sagawa (International Journal of Refrigeration, 2023)

Seasonal habitat use by warmwater fishes in a braided river, southwestern Japan: effects of spatiotemporal thermal heterogeneity - Daisuke Togaki; Mikio Inoue; Kentaro Ikari (Ichthyological Research, 2023)

Diverse heliorhodopsins detected via functional metagenomics in freshwater Actinobacteria , Chloroflexi and Archaea - Ariel Chazan; Andrey Rozenberg; Kentaro Mannen; Takashi Nagata; Ran Tahan; Shir Yaish; Shirley Larom; Keiichi Inoue; Oded Béjà; Alina Pushkarev (Environmental Microbiology, 2022)
Summary The recently discovered rhodopsin family of heliorhodopsins (HeRs) is abundant in diverse microbial environments. So far, the functional and biological roles of HeRs remain unknown. To tackle this issue, we combined experimental and computational screens to gain some novel insights. Here, 10 readily expressed HeR genes were found using functional metagenomics on samples from two freshwater environments. These HeRs originated from diverse prokaryotic groups: Actinobacteria , Chloroflexi and Archaea . Heterologously expressed HeRs absorbed light in the green and yellow wavelengths (543–562 nm) and their photocycles exhibited diverse kinetic characteristics. To approach the physiological function of the HeRs, we used our environmental clones along with thousands of microbial genomes to analyze genes neighbouring HeRs. The strongest association was found with the DegV family involved in activation of fatty acids, which allowed us to hypothesize that HeRs might be involved in light‐induced membrane lipid modifications.

Management of regional bone bank during declaration of a state of emergency concerning the COVID-19 in Japan - Kentaro Uchida; Manabu Mukai; Masayuki Miyagi; Kensuke Fukushima; Katsufumi Uchiyama; Akiko Nakayama; Mai Matsumoto; Naonobu Takahira; Ken Urabe; Masashi Takaso; Gen Inoue (Cell and Tissue Banking, 2021)

New microsatellite markers for Ellipse, Venustaconcha ellipsiformis (Bivalvia: Unionidae), with notes on optimal sample size and cross-species amplification - Kentaro Inoue; Bernard E. Sietman; Stephen E. McMurray; J. Scott Faiman; David T. Zanatta (Molecular Biology Reports, 2021)

Integrative taxonomy reveals a new species of freshwater mussel, Potamilus streckersoni sp. nov. (Bivalvia: Unionidae): implications for conservation and management - Chase H. Smith; Nathan A. Johnson; Kentaro Inoue; Robert D. Doyle; Charles R. Randklev (Systematics and Biodiversity, 2019)

Development of a new benzodiazepine hypnotics withdrawal symptom scale - Mina Kobayashi; Isa Okajima; Hajime Narisawa; Takashi Kikuchi; Kentaro Matsui; Ken Inada; Jun Ishigooka; Yuichi Inoue (Sleep and Biological Rhythms, 2018)

Brain microstructural alterations in patients with severe obstructive sleep apnea: a preliminary diffusion tensor imaging study - Masaki Nakamura; Mariko Yanagihara; Kentaro Matsui; Mina Kobayashi; Yuichi Inoue (Sleep and Biological Rhythms, 2017)

Predicting the effects of climate change on population connectivity and genetic diversity of an imperiled freshwater mussel, Cumberlandia monodonta (Bivalvia: Margaritiferidae), in riverine systems - Kentaro Inoue; David J. Berg (Global Change Biology, 2017)
In the face of global climate change, organisms may respond to temperature increases by shifting their ranges poleward or to higher altitudes. However, the direction of range shifts in riverine systems is less clear. Because rivers are dendritic networks, there is only one dispersal route from any given location to another. Thus, range shifts are only possible if branches are connected by suitable habitat, and stream‐dwelling organisms can disperse through these branches. We used Cumberlandia monodonta (Bivalvia: Unionoida: Margaritiferidae) as a model species to investigate the effects of climate change on population connectivity because a majority of contemporary populations are panmictic. We combined ecological niche models ( ENM s) with population genetic simulations to investigate the effects of climate change on population connectivity and genetic diversity of C. monodonta . The ENM s were constructed using bioclimatic and landscape data to project shifts in suitable habitat under future climate scenarios. We then used forward‐time simulations to project potential changes in genetic diversity and population connectivity based on these range shifts. ENM results under current conditions indicated long stretches of highly suitable habitat in rivers where C. monodonta persists; populations in the upper Mississippi River remain connected by suitable habitat that does not impede gene flow. Future climate scenarios projected northward and headwater‐ward range contraction and drastic declines in habitat suitability for most extant populations throughout the Mississippi River Basin. Simulations indicated that climate change would greatly reduce genetic diversity and connectivity across populations. Results suggest that a single, large population of C. monodonta will become further fragmented into smaller populations, each of which will be isolated and begin to differentiate genetically. Because C. monodonta is a widely distributed species and purely aquatic, our results suggest that persistence and connectivity of stream‐dwelling organisms will be significantly altered in response to future climate change.

Thrombolysis with Low-Dose Tissue Plasminogen Activator 3–4.5 h After Acute Ischemic Stroke in Five Hospital Groups in Japan - Ryuta Morihara; Syoichiro Kono; Kota Sato; Nozomi Hishikawa; Yasuyuki Ohta; Toru Yamashita; Kentaro Deguchi; Yasuhiro Manabe; Yoshiki Takao; Kenichi Kashihara; Satoshi Inoue; Hideki Kiriyama; et al. (Translational Stroke Research, 2016)

The effect of comorbidity of restless legs syndrome and migraine on sleep and mood: an integration of multicenter data - Keisuke Suzuki; Masayuki Miyamoto; Tomoyuki Miyamoto; Shiho Suzuki; Yuichi Inoue; Momoyo Murata; Kentaro Matsui; Shingo Nishida; Kenichi Hayashida; Akira Usui; Yoichiro Ueki; Masaki Nakamura; et al. (Sleep and Biological Rhythms, 2016)

Differential effects of docoosahexaenoic and arachidonic acid on fatty acid composition and myosin heavy chain-related genes of slow- and fast-twitch skeletal muscle tissues - Michio Hashimoto; Takayuki Inoue; Masanori Katakura; Shahdat Hossain; Abdullah Al Mamun; Kentaro Matsuzaki; Hiroyuki Arai; Osamu Shido (Molecular and Cellular Biochemistry, 2016)

Utilization of light by fucoxanthin–chlorophyll-binding protein in a marine centric diatom, Chaetoceros gracilis - Tomoko Ishihara; Kentaro Ifuku; Eiki Yamashita; Yuko Fukunaga; Yuri Nishino; Atsuo Miyazawa; Yasuhiro Kashino; Natsuko Inoue-Kashino (Photosynthesis Research, 2015)

Past climate change drives current genetic structure of an endangered freshwater mussel species - Kentaro Inoue; Brian K. Lang; David J. Berg (Molecular Ecology, 2015)
Historical‐to‐recent climate change and anthropogenic disturbance affect species distributions and genetic structure. The Rio Grande watershed of the United States and Mexico encompasses ecosystems that are intensively exploited, resulting in substantial degradation of aquatic habitats. While significant anthropogenic disturbances in the Rio Grande are recent, inhospitable conditions for freshwater organisms likely existed prior to such disturbances. A combination of anthropogenic and past climate factors may contribute to current distributions of aquatic fauna in the Rio Grande basin. We used mitochondrial DNA and 18 microsatellite loci to infer evolutionary history and genetic structure of an endangered freshwater mussel, P openaias popeii , throughout the Rio Grande drainage. We estimated spatial connectivity and gene flow across extant populations of P . popeii and used ecological niche models ( ENM s) and approximate B ayesian computation ( ABC ) to infer its evolutionary history during the Pleistocene. structure results recovered regional and local population clusters in the Rio Grande. ENM s predicted drastic reductions in suitable habitat during the last glacial maximum. ABC analyses suggested that regional population structure likely arose in this species during the mid‐to‐late Pleistocene and was followed by a late Pleistocene population bottleneck in New Mexico populations. The local population structure arose relatively recently, perhaps due to anthropogenic factors. P openaias popeii , one of the few freshwater mussel species native to the Rio Grande basin, is a case study for understanding how both geological and anthropogenic factors shape current population genetic structure. Conservation strategies for this species should account for the fragmented nature of contemporary populations.

A stable and efficient nuclear transformation system for the diatom Chaetoceros gracilis - Kentaro Ifuku; Dongyi Yan; Mado Miyahara; Natsuko Inoue-Kashino; Yoshiharu Y. Yamamoto; Yasuhiro Kashino (Photosynthesis Research, 2015)

Identification and characterization of 12 microsatellite loci for Physa in the Chihuahuan Desert - Kofi N. Ansah; Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite markers for the Texas hornshell, Popenaias popeii (Bivalvia: Unionidae), through next-generation sequencing - Kentaro Inoue; Brian K. Lang; David J. Berg (Conservation Genetics Resources, 2013)

OEP80, an essential protein paralogous to the chloroplast protein translocation channel Toc75, exists as a 70-kD protein in the Arabidopsis thaliana chloroplast outer envelope - Shih-Chi Hsu; Mehdi Nafati; Kentaro Inoue (Plant Molecular Biology, 2012)

Expression, subcellular localization, and cis-regulatory structure of duplicated phytoene synthase genes in melon (Cucumis melo L.) - Xiaoqiong Qin; Ardian Coku; Kentaro Inoue; Li Tian (Planta, 2011)

Isolation and characterization of 17 polymorphic microsatellite loci in the spectaclecase, Cumberlandia monodonta (Bivalvia: Margaritiferidae) - Kentaro Inoue; Gregory R. Moyer; Ashantyé Williams; Emy M. Monroe; David J. Berg (Conservation Genetics Resources, 2011)

Molecular identification of 1-Cys peroxiredoxin and anthocyanidin/flavonol 3-O-galactosyltransferase from proanthocyanidin-rich young fruits of persimmon (Diospyros kaki Thunb.) - Ayako Ikegami; Takashi Akagi; Daniel Potter; Masahiko Yamada; Akihiko Sato; Keizo Yonemori; Akira Kitajima; Kentaro Inoue (Planta, 2009)

Two chloroplastic protein translocation components, Tic110 and Toc75, are conserved in different plastid types from multiple plant species - Jennifer A. Dávila-Aponte; Kentaro Inoue; Kenneth Keegstra (Plant Molecular Biology, 2003)

Effect of the invasion of vascular plants on heat and water balance in the Sarobetsu mire, northern Japan - Kentaro Takagi; Taro Tsuboya; Hidenori Takahashi; Takashi Inoue (Wetlands, 1999)

Immunolocalization of two ligninO-methyltransferases in stems of alfalfa (Medicago sativa L.) - Rossio Kersey; Kentaro Inoue; Karel R. Schubert; Richard A. Dixon (Protoplasma, 1999)

Oculomotor sequence learning: a positron emission tomography study - R. Kawashima; J. Tanji; K. Okada; Motoaki Sugiura; Kazunori Sato; Shigeo Kinomura; Kentaro Inoue; Akira Ogawa; Hiroshi Fukuda (Experimental Brain Research, 1998)